Correction of Microtubule-Kinetochore Attachment Errors: Mechanisms and Role in Tumor suppression - Ricke, Robin M. (2011)
During mitosis, cells segregate duplicated chromosomes with high fidelity in order to maintain genome stability. Proper attachment of sister kinetochores to spindle microtubules is critical for accurate chromosome segregation and is driven by complex mechanisms that promote the capture of unattached kinetochores and the resolution of erroneously attached kinetochores. Defects in these surveillance systems promote chromosome segregation and aneuploidy and can contribute to neoplastic transformation. Understanding, how, at the molecular level, accurate chromosome segregation is achieved may be crucial for our understanding of how cancer cells develop genome instability.